(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
In the conduct of business activities, the promotion of business ideas, the organization of business activities from the practical (organizational, technical and technological) side, the provision and provision of industry information for the relevant activity, as well as the analysis of information related to this industry are of particular importance. Entrepreneurial activity is divided into certain types based on the specified circumstances, according to the coverage of one or another aspect. At the same time, these types of entrepreneurial activities demonstrate the possession of certain competencies. Mastering the appropriate set of competencies creates an opportunity for the effective and successful organization of a certain type of entrepreneurial activity. The article talks about the types of entrepreneurial activity and related competencies.